Voltage control of hybrid energy sources for microgrid employing biomass-solar-wind - Badruhisham, Saidatul Haneen; Abu Hanifah, Mohd Shahrin; Yusoff, Siti Hajar; Hasbullah, Nurul Fadzlin; Yaacob, Mashkuri (Inderscience Publishers, 2023)
Renewable energy (RE) systems have the potential to meet future electricity demand. Solar, wind, and biomass (BM) have recently gained attention in providing electricity, and their integrations have evolved into a microgrid. However, integrating these RE into one system is challenging and none of the previous research focuses on voltage control for this microgrid. Therefore, this paper proposed a suitable hybrid renewable energy sources (RES) architecture for microgrids employing BM-solar photovoltaic (PV)-wind with voltage controller. A test model with single RES is simulated in the MATLAB-Simulink software, and each RES result is compared to the benchmarking paper. A PI controller is proposed in the hybrid microgrid for voltage stability. For that, the microgrid generates an average total of 777 kW from these RES The results of THD values are compared between the microgrid with and without the PI controller. As a result, the THD value for voltage and current are reduced by 25.26% and 26.20%, respectively, proving that the PI controller can control the voltage stability of the microgrid